2021
DOI: 10.1111/andr.13104
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of botulinum neurotoxin in the treatment of erectile dysfunction refractory to phosphodiesterase inhibitors: Results of a randomized controlled trial

Abstract: Background: There has been recent interest in the use of botulinum neurotoxin (BoNT) in the field of Andrology, whereby it has been investigated in the treatment of penile retraction and premature ejaculation.Objectives: To evaluate the safety and efficacy of intracavernosal BoNT-A injection in the treatment of patients with erectile dysfunction (ED) refractory to oral phosphodiesterase inhibitors (PDE5Is). Patients and methods: A double-blind randomized placebo-controlled prospective comparative study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Since the potency of Botox ® and Xeomin ® is identical, they can be compared using a 1:1 conversion ratio [21]. Studies have repeatedly reported the effectiveness of a 100U dose of onabotulinumtoxinA in difficult-to-treat ED [14,16,17]; therefore, we used the same dose of incobotulinumtoxinA in the present study. The conversion ratio between onabotulinumtoxinA (or incobotulinumtoxinA) and abobotulinumtoxinA is more debated [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the potency of Botox ® and Xeomin ® is identical, they can be compared using a 1:1 conversion ratio [21]. Studies have repeatedly reported the effectiveness of a 100U dose of onabotulinumtoxinA in difficult-to-treat ED [14,16,17]; therefore, we used the same dose of incobotulinumtoxinA in the present study. The conversion ratio between onabotulinumtoxinA (or incobotulinumtoxinA) and abobotulinumtoxinA is more debated [20].…”
Section: Discussionmentioning
confidence: 99%
“…The first follow-up assessment was performed 43.5 (34-71) days post-injection. EFdomain score post-injection was 21 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). A total of 28/54 (52%) men responded: their EF domain score was 26 (22)(23)(24)(25)(26)(27)(28)(29), corresponding to an increase of 8 (6-15) points from baseline.…”
Section: Response To the First Incobotulinumtoxina Icimentioning
confidence: 99%
See 3 more Smart Citations